A high-temperature-resistant two-component waterborne polyurethane adhesive as well as a preparation method and application thereof
Patent Information
- Application Number
- CN202411937069.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2026-10-13
AI Technical Summary
但水性聚氨酯欲获得较好的耐高温性能,仍需要对聚氨酯进行改性,但大部分的改性研究都只是针对某一个缺陷的,而能同时提高耐水性、耐高温性和断裂伸长率等性能的研究很少
[0038]本发明提供了一种耐高温、双组分水性聚氨酯胶黏剂及其制备方法和应用。具备以下有益效果:
Smart Images

Figure CN122898239A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of textile auxiliaries technology, specifically to a high-temperature resistant, two-component waterborne polyurethane adhesive, its preparation method, and its application. Background Technology
[0003] The finishing and processing stages of textile printing and dyeing effectively improve the quality and added value of textiles, making it an indispensable and crucial link in the entire textile industry chain. The textile finishing industry involves the extensive use of adhesives, with most finishing companies primarily using solvent-based adhesives, which are also a major source of volatile organic compounds (VOCs). Practice has proven that implementing source substitution of raw and auxiliary materials with low VOC content is the best way to achieve environmental compliance and governance in the textile finishing industry.
[0004] Polyurethane is short for polyurethane, generally defined as a polymer compound containing repeating urethane groups (-NHCOO-) on its main chain. It is typically formed by the stepwise polymerization of binary or polyisocyanates with compounds containing two or more reactive hydrogen atoms (Xu Gewen et al., Waterborne Polyurethane Materials [M. Beijing: Chemical Industry Press, 2006: 1-3.). It is an elastic material between general rubber and plastics, possessing both the high elasticity of rubber and the high strength of plastics. It has a high elongation and a wide range of hardness. Simultaneously, polyurethane elastomers also exhibit excellent impact resistance, low-temperature resistance, ozone resistance, radiation resistance, as well as load-bearing capacity, heat insulation, and electrical insulation properties. However, its heat resistance and mechanical properties are poor. At temperatures of 80–90°C (Tsai MT, Huang SL, Liu SJ, et al. Synthesis and properties of poly(urethane-imide) interpenetrating network membranes fJl. Desalination, 2008, 233: 191-200.), some key mechanical properties such as modulus and strength decrease significantly. When the processing temperature reaches or exceeds 200°C (Sarier N, Onder E. Thermal characteristics of polyurethane foams incorporated with phase-changed materials[J]. Thermochim Acta, 2007, 454: 90-98.), polyurethane undergoes thermal degradation, falling far short of the requirements for high-temperature resistant materials. This, to some extent, limits the application of polyurethane (Park SH, Chung ID, Hartwig A, et al. Hydrolytic stability and physical properties of waterborne polyurethane based on hydrolytically stable polyol[J]. Colloids and SurfacesA: Physicochemical (Engineering Aspects, 2007, 305: 126-131) Therefore, modifying the heat resistance and improving the mechanical properties of polyurethane through various means has become a research hotspot both domestically and internationally.
[0005] For many years, research institutions and researchers in my country have conducted in-depth research on the modification of waterborne polyurethane adhesives, aiming to improve the heat resistance of waterborne polyurethane, address its shortcomings, and expand its application areas. Currently, the main methods for improving waterborne polyurethane adhesives both domestically and internationally include epoxy resin modification, silicone modification, and acrylic modification. ( H, Yalcinyuva T, zgümüs S. A novel type of Si-containing poly(urethane-imide)s: synthesis, characterization and electrical properties[J]. Eur Polym J, 2005, 41: 771-781.) et al. obtained NCO-terminated PU prepolymers using 2,4-toluene diisocyanate and diphenyldisilol, and then reacted them with benzophenone dianhydride (BTDA) and pyromellitic anhydride (PMDA) at high temperatures to obtain PUI polymers with excellent high-temperature resistance. Thermogravimetric analysis showed that the thermal decomposition temperature of PUI polymers was significantly higher than that of pure polyurethane. Although silicon was also introduced into the molecular chain, it was found that the introduction of silicon had little effect on stability, thus indicating that the addition of polyimide can significantly improve the heat resistance of polyurethane. Takeichi (Takeichi T, Ujiie K, Ilnoue K. High performance poly(urethane-imide) prepared by introducing imide blocks into the polyurethane backbone[J]. Polymer, 2005, 46: 11225-11231.) et al. prepared PU prepolymer by reacting poly(hexamethylene adipate) diol (PEA) with excess TDI, and then reacted it with amino-terminated oligomers containing imide structures to prepare PUI. The study found that the introduction of imide groups increased the tensile modulus of the copolymer, while decreasing the elongation at break. Simultaneously, the introduction of imide improved the polymer's heat resistance; the temperature at which weight loss by 10 wt% increased from 280℃ to 295℃, and this increase further increased with increasing imide content. Yeganeh (Yeganeh H, Barikani M, Khodabadi FN. Synthesis and properties of novel thermoplastic poly(urethane-imide)s[J]. Eur Polym J, 2000, 36: 2207-2211.) et al. first synthesized a hydroxyl-terminated prepolymer containing an imide structure, and then reacted it with an NCO-PU prepolymer obtained by reacting TDI and polyester diol to synthesize PUI thermoplastic elastomer. TG tests showed that the PUI synthesized by this method had a 10 wt% weight loss temperature above 310℃. DSC showed that, due to the presence of an imide structure in the molecular chain, the glass transition temperature of the hard segment of this polymer increased from 75℃ to 110℃ compared to pure PU.Avadhani (Avadhani CV, Wadgaonkar Pp, Khisti RS, et al. Synthesis and characterization of imide-containing diisocyanates and poly(imide-urethane)s thereform[J]. Polym Bull 1990, 23: 163-169.) et al. synthesized diisocyanates containing imide groups using amino acids and dianhydrides via Curtius rearrangement, and then prepared PUI with polyether diols. The results showed that the thermal stability of the product was significantly improved due to the introduction of imide groups into the molecular chain, with an initial decomposition temperature as high as 215℃. However, to obtain better high-temperature resistance, waterborne polyurethane still needs modification. Most modification studies only target a single defect, and there are very few studies that can simultaneously improve water resistance, high-temperature resistance, and elongation at break. Summary of the Invention
[0006] (a) Technical problems to be solved
[0007] To address the shortcomings of existing technologies, this invention provides a high-temperature resistant, two-component waterborne polyurethane adhesive, its preparation method, and its application. The two-component waterborne polyurethane adhesive uses organic polyisocyanates, high-temperature resistant polyether polyols, and their silane coupling agents as main raw materials to prepare waterborne polyurethane (component A); a curing agent (component B) is prepared using hydroxyl-terminated compounds as main raw materials. By compounding components A and B, the water resistance, high-temperature resistance, and elongation at break are simultaneously improved, solving the problems mentioned in the background art.
[0008] (II) Technical Solution
[0009] To achieve the above objectives, the present invention provides the following technical solution:
[0010] According to a first aspect of the present invention, a high-temperature resistant, two-component waterborne polyurethane adhesive is provided, comprising component A and component B;
[0011] Component A, by mass percentage, comprises 10-20% organic polyisocyanate, 10-20% polyol, 0.1-1% catalyst, 2-6% chain extender, 3-8% end-capping monomer, 2-8% organic solvent, 1-3% salt-forming agent, and the balance being water.
[0012] Component B, by mass percentage, comprises 10-15% organic polyisocyanate, 10-18% polyol, 2-8% organic solvent, and the balance being water.
[0013] This invention is produced by a prepolymer method to synthesize a waterborne polyurethane adhesive with polyols as soft segments and organic polyisocyanates as hard segments. When applied to hot stamping processes, it can effectively impart good high-temperature resistance and washability to hot stamping fabrics. In addition, the high-temperature fastness of hot stamping fabrics is significantly improved, and good brightness is still maintained even when the hot stamping plate is 190°C for 15 seconds.
[0014] Preferably, in component A, the organic polyisocyanate is selected from at least one of toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate;
[0015] The polyol is selected from at least one of polyethylene glycol 2000, polytetrahydrofuran glycol 2000, and polycarbonate glycol 2000.
[0016] Preferably, in component A, the catalyst is selected from at least one of dibutyltin dilaurate and stannous octoate;
[0017] The chain extender is selected from at least one of dimethylolpropionic acid, dimethylolbutyric acid, sodium ethylenediamine ethanesulfonate, or 1,4-butanediol.
[0018] The end-capping monomer is selected from at least one of aminopropyltrimethoxysiloxane, glycidoxypropyltrimethoxysilane, and aminopropyltriethoxysilane.
[0019] The salt-forming agent is selected from any one of triethylamine, sodium hydroxide, or ammonia water;
[0020] The organic solvent is selected from any one of butanone, tetrahydrofuran, and N-methylpyrrolidone.
[0021] Preferably, in component B, the organic polyisocyanate is selected from at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, 2,6-toluene diisocyanate or hexamethylene diisocyanate;
[0022] The polyol is selected from at least one of polyethylene glycol 2000, polytetrahydrofuran glycol, ethylene glycol or trimethylolpropane;
[0023] The organic solvent is selected from any one of butanone, tetrahydrofuran, or N-methylpyrrolidone.
[0024] According to a second aspect of the present invention, a method for preparing a high-temperature resistant, two-component waterborne polyurethane adhesive is provided, comprising the following steps:
[0025] (1) Under the action of a catalyst, organic polyisocyanate and dehydrated polyol are mixed to carry out the first reaction. When the -NCO content in the reaction system reaches the theoretical value, a chain extender is added to carry out the second reaction. Then, a capping monomer is added to carry out the capping reaction. Then, a salting agent and an organic solvent are added to carry out the neutralization reaction. Finally, water is added to carry out emulsification and dispersion, and vacuum distillation is performed to obtain component A.
[0026] (2) The organic polyisocyanate, the dehydrated polyol and the organic solvent are mixed and carried out in the third reaction to obtain component B;
[0027] (3) The components A and B are compounded to obtain the high-temperature resistant, two-component waterborne polyurethane adhesive.
[0028] Preferably, in step (1), the temperature of the first reaction is 60-100°C, and the reaction time is 2-3.5 h;
[0029] The temperature of the second reaction is 60–100°C, and the reaction time is 0.5–2 hours.
[0030] The end-capping reaction is carried out at a temperature of 60–100°C for 0.5–1 hour.
[0031] The neutralization reaction occurs at a temperature of 60–100°C for 0.5–1 hour.
[0032] The emulsification and dispersion time is 0.5 to 1 hour.
[0033] Preferably, in step (2), the temperature of the third reaction is 70-90°C and the time of the third reaction is 2-3.5h.
[0034] According to a third aspect of the present invention, a high-temperature resistant, two-component waterborne polyurethane adhesive is provided for use in hot stamping finishing of textiles.
[0035] Specifically, a coating process is used. After the hot stamping material is glued to the fabric, it is bonded together and baked in a calender at 80-200℃ for 2-15 seconds to obtain the hot stamping finished fabric.
[0036] This invention applies a high-temperature resistant, two-component water-based polyurethane adhesive to the fabric after hot stamping, resulting in a surface pattern with good fastness. The wash fastness can reach level three, and it still has excellent brightness under the conditions of 190°C and 15s on a heat press.
[0037] (III) Beneficial Effects
[0038] This invention provides a high-temperature resistant, two-component waterborne polyurethane adhesive, its preparation method, and its application. It offers the following advantages:
[0039] (1) The present solution provides a high temperature resistant, two-component waterborne polyurethane adhesive. The organic polyisocyanate in component A reacts with polyol and water to form a homogeneous film with mechanical properties. Component B and the uncured functional groups in component A gradually polymerize or catalytically polymerize to generate a three-dimensional network structure, which further improves the mechanical properties of the homogeneous film. By controlling the content of each substance in component A and component B, it has excellent water resistance, high temperature resistance and elongation at break.
[0040] (2) The high-temperature resistant, two-component waterborne polyurethane adhesive provided by this solution has low raw material cost and is green and environmentally friendly. It can solve the problems of non-environmental protection of organic solvent system, high cost of ordinary waterborne polyurethane, and poor high temperature resistance and poor wash fastness of fabric surface pattern after hot stamping. It can replace oil-based resin adhesive materials, reduce the pressure of organic solvent volatilization and production safety issues during the production process, and is environmentally friendly, safe and clean.
[0041] (3) The present solution provides a method for preparing a high-temperature resistant, two-component waterborne polyurethane adhesive. By simply blending component A and component B, a waterborne polyurethane adhesive with excellent comprehensive performance can be prepared. Attached Figure Description
[0042] Figure 1 This is a particle size distribution diagram of component A in Example 1 of the present invention;
[0043] Figure 2 This is a particle size distribution diagram of component B in Example 1B of the present invention;
[0044] Figure 3 This is a Zeta potential distribution diagram of component A in Example 1 of the present invention;
[0045] Figure 4 This is a Zeta potential distribution diagram of component B in Example 1 of the present invention. Detailed Implementation
[0046] To better illustrate the content of this invention, the following description is provided in conjunction with specific embodiments.
[0047] This invention provides a high-temperature resistant, two-component waterborne polyurethane adhesive. By physically mixing the high-temperature resistant waterborne polyurethane adhesive (component A) and a curing agent with terminal hydroxyl compounds (component B), a high-temperature resistant, two-component waterborne polyurethane adhesive suitable for continuous hot stamping processes is obtained. The specific steps include:
[0048] (1) Preparation of component A:
[0049] Organic polyisocyanates and dehydrated polyols were added to a four-necked flask equipped with an electric stirrer, a reflux condenser, a thermometer, and nitrogen protection. A catalyst was added, and the mixture was heated to 60–80 °C under N2 protection for 2–3.5 h. When the -NCO content in the reaction system reached the theoretical value, a chain extender was added, and the reaction was continued for 0.5–2 h. Then, a terminal monomer was added, and the reaction was continued for 0.5–1 h. A salt-forming agent was added for neutralization reaction for 0.5–1 h. During this period, if the system became too viscous, an appropriate amount of organic solvent was added to reduce the viscosity. Water was added under high-speed stirring for emulsification and dispersion for 0.5–1 h. The reaction was then stopped, and the organic solvent was removed by vacuum distillation and the mixture was cooled to room temperature (25 °C).
[0050] (2) Preparation of component B:
[0051] Organic polyisocyanate, dehydrated polyol and organic solvent were added to a four-necked flask equipped with an electric stirrer, reflux condenser, thermometer and nitrogen protection device. The mixture was stirred uniformly at 70-90°C for 2-3.5 hours, and then the reaction was stopped and cooled to room temperature (25°C).
[0052] (3) Preparation of high-temperature resistant, two-component waterborne polyurethane adhesive:
[0053] Add component A and component B to a beaker in a certain proportion and stir at room temperature for 10 minutes to obtain a high-temperature resistant, two-component waterborne polyurethane adhesive.
[0054] (4) Applications in fabric finishing:
[0055] According to the designed dosage, dilute the high-temperature resistant, two-component waterborne polyurethane adhesive with water to the target viscosity, stir evenly and set aside for use.
[0056] A coating process is used to apply a uniform layer of adhesive to the fabric or hot stamping material. Another piece of fabric of the same size is then attached to the fabric coated with adhesive and hot-pressed once at 130°C in a calender to obtain two finished fabrics.
[0057] In one specific embodiment, component A, by mass fraction, includes the following components:
[0058]
[0059] The remaining component is deionized water;
[0060] Component B, by mass fraction, includes the following components:
[0061] Organic polyisocyanates: 10%-15%;
[0062] Polyols: 10%-18%;
[0063] Organic solvents: 2%-8%;
[0064] The remaining component is deionized water.
[0065] The following specific embodiments further illustrate the high-temperature resistant, two-component waterborne polyurethane adhesive of the present invention.
[0066] Example 1
[0067] 17 kg of hexamethylene diisocyanate was mixed with 10 kg of dehydrated polycarbonate diol 2000, and 0.5 kg of dibutyltin dilaurate was added. The mixture was heated to 80 °C under N2 protection and reacted for 3 h. When the -NCO in the system reached the theoretical value, 5 kg of dimethylolbutyric acid was added and the reaction was continued for 1 h. Then, 5 kg of aminopropyltrimethoxysiloxane was added and the reaction was continued for 0.5 h. Then, 1 kg of triethylamine was added for neutralization reaction for 1 h. During this period, because the system was too viscous, 2 kg of butanone was added to reduce the viscosity. Then, 59.5 kg of water was added under high speed stirring to emulsify and disperse for 0.5 h. After the reaction was stopped, butanone was removed by vacuum distillation and cooled to room temperature to obtain component A.
[0068] 14 kg of hexamethylene diisocyanate, 14 kg of dehydrated ethylene glycol, 2 kg of acetone and 70 kg of water were added to a four-necked flask equipped with an electric stirrer, a reflux condenser, a thermometer and a nitrogen protection device. The mixture was stirred uniformly at 80 °C for 3 h. After the reaction was stopped, the temperature was lowered to room temperature of 25 °C to obtain component B.
[0069] Mix 100 kg of component A with 5 kg of component B and stir at room temperature for 10 min to obtain a high-temperature resistant, two-component waterborne polyurethane adhesive with a viscosity of 13500 mPa·s.
[0070] Particle size distribution and site distribution tests were performed on components A and B in this embodiment, respectively. Figure 1 The particle size distribution curve for component A is shown below. Figure 2 The particle size distribution curve of component B is shown below. Figure 1 and Figure 2 It can be seen that the particle size of component A is 54.4 nm and the particle size of component B is 54.9 nm. Due to the smaller particle size, it is easier to pass through the fiber, and the contact area with the fiber is increased, thereby improving the fiber's adhesion ability.
[0071] Figure 3 The Zeta potential distribution curve for component A is shown. Figure 4 The Zeta potential distribution curve for component B is shown below. Figure 3 and Figure 4It can be seen that the Zeta potential of component A is -54.4 mV and that of component B is -54.6 mV, both of which have absolute values greater than 30 mV, indicating that the emulsion has good stability. The electrostatic repulsion between particles is sufficient to resist the van der Waals attraction between particles, making it difficult for particles to aggregate.
[0072] Example 2
[0073] 18 kg of 2,4-toluene diisocyanate was mixed with 12 kg of dehydrated polyethylene glycol 2000, and 0.3 kg of dibutyltin dilaurate was added. The mixture was heated to 80 °C under N2 protection and reacted for 3 h. When the -NCO in the system reached the theoretical value, 5 kg of dimethylolpropionic acid was added and the reaction was continued for 1 h. Then, 5 kg of aminopropyltrimethoxysiloxane was added and the reaction was continued for 0.5 h. Then, 1 kg of triethylamine was added for neutralization reaction for 1 h. During this period, because the system was too viscous, 2 kg of butanone was added to reduce the viscosity. Then, 56.7 kg of water was added under high-speed stirring to emulsify and disperse for 0.5 h. After the reaction was stopped, butanone was removed by vacuum distillation and cooled to room temperature to obtain component A.
[0074] 12 kg of 2,4-toluene diisocyanate, 12 kg of dehydrated polyethylene glycol 2000, 2 kg of acetone, and 74 kg of water were added to a four-necked flask equipped with an electric stirrer, a reflux condenser, a thermometer, and a nitrogen protection device. The mixture was stirred uniformly at 80°C for 3 hours. After the reaction was stopped, the temperature was lowered to room temperature (25°C) to obtain component B.
[0075] Mix 100 kg of component A with 2 kg of component B and stir at room temperature for 10 min to obtain a high-temperature resistant, two-component waterborne polyurethane adhesive with a viscosity of 10500 mPa·s.
[0076] Example 3
[0077] 20 kg of isophorone diisocyanate was mixed with 15 kg of dehydrated polytetrahydrofuran diol 2000, and 0.2 kg of stannous octoate was added. The mixture was heated to 80 °C under N2 protection and reacted for 3 h. When the -NCO in the system reached the theoretical value, 4 kg of dimethylolpropionic acid was added and the reaction was continued for 1 h. Then, 5 kg of aminopropyltrimethoxysiloxane was added and the reaction was continued for 0.5 h. Then, 2 kg of sodium hydroxide was added for neutralization reaction for 1 h. During this period, due to the excessive viscosity of the system, 2 kg of tetrahydrofuran was added to reduce the viscosity. Then, 51.8 kg of water was added under high-speed stirring to emulsify and disperse for 0.5 h. After the reaction was stopped, tetrahydrofuran was removed by vacuum distillation and the mixture was cooled to room temperature to obtain component A.
[0078] 12 kg of isophorone diisocyanate, 13 kg of dehydrated polytetrahydrofurandiol, 2 kg of N-methylpyrrolidone and 73 kg of water were added to a four-necked flask equipped with an electric stirrer, a reflux condenser, a thermometer and a nitrogen protection device. The mixture was stirred uniformly at 80 °C for 3 h. After the reaction was stopped, the temperature was lowered to room temperature of 25 °C to obtain component B.
[0079] Mix 100 kg of component A with 4 kg of component B and stir at room temperature for 10 min to obtain a high-temperature resistant, two-component waterborne polyurethane adhesive with a viscosity of 12000 mPa·s.
[0080] Example 4
[0081] 16 kg of diphenylmethane diisocyanate was mixed with 13 kg of dehydrated polycarbonate diol 2000, and 0.6 kg of dibutyltin dilaurate was added. The mixture was heated to 80 °C under N2 protection and reacted for 3 h. When the -NCO in the system reached the theoretical value, 4 kg of dimethylolpropionic acid was added and the reaction was continued for 1 h. Then, 5 kg of aminopropyltrimethoxysiloxane was added and the reaction was continued for 0.5 h. Then, 2 kg of ammonia was added for neutralization reaction for 1 h. During this period, because the system was too viscous, 2 kg of N-methylpyrrolidone was added to reduce the viscosity. Then, 57.4 kg of water was added under high speed stirring to emulsify and disperse for 0.5 h. After the reaction was stopped, N-methylpyrrolidone was removed by vacuum distillation and cooled to room temperature to obtain component A.
[0082] 15 kg of diphenylmethane diisocyanate, 15 kg of dehydrated polycarbonate diol 2000, 2 kg of N-methylpyrrolidone and 68 kg of water were added to a four-necked flask equipped with an electric stirrer, a reflux condenser, a thermometer and a nitrogen protection device. The mixture was stirred uniformly at 80 °C for 3 h. After the reaction was stopped, the temperature was lowered to room temperature of 25 °C to obtain component B.
[0083] Mix 100 kg of component A with 5.9 kg of component B and stir at room temperature for 10 min to obtain a high-temperature resistant, two-component waterborne polyurethane adhesive with a viscosity of 14000 mPa·s.
[0084] Example 5
[0085] 15 kg of 2,6-toluene diisocyanate was mixed with 14 kg of dehydrated polytetrahydrofurandiol 2000, and 0.8 kg of stannous octoate was added. The mixture was heated to 80 °C under N2 protection and reacted for 3 h. When the -NCO in the system reached the theoretical value, 5 kg of dimethylolbutyric acid was added and the reaction was continued for 1 h. Then, 5 kg of aminopropyltrimethoxysiloxane was added and the reaction was continued for 0.5 h. Then, 1 kg of triethylamine was added for neutralization reaction for 1 h. During this period, because the system was too viscous, 2 kg of butanone was added to reduce the viscosity. Then, 57.2 kg of water was added under high-speed stirring to emulsify and disperse for 0.5 h. After the reaction was stopped, butanone was removed by vacuum distillation and cooled to room temperature to obtain component A.
[0086] 13 kg of 2,6-toluene diisocyanate, 12 kg of dehydrated polycarbonate diol 2000, 2 kg of acetone and 73 kg of water were added to a four-necked flask equipped with an electric stirrer, a reflux condenser, a thermometer and a nitrogen protection device. The mixture was stirred uniformly at 80 °C for 3 h. After the reaction was stopped, the temperature was lowered to room temperature of 25 °C to obtain component B.
[0087] Mix 100 kg of component A with 6.7 kg of component B and stir at room temperature for 10 min to obtain a high-temperature resistant, two-component waterborne polyurethane adhesive with a viscosity of 14500 mPa·s.
[0088] Comparative Example 1
[0089] The difference between this comparative example and Example 1 is that it contains only component A.
[0090] Comparative Example 2
[0091] The difference between this comparative example and Example 1 is that it contains only component B.
[0092] Application examples
[0093] Using a coating process, a layer of adhesive from Examples 1 to 5, as well as Comparative Examples 1 and 2, is coated onto the hot stamping material. Then, another piece of fabric of the same size is attached to the material coated with adhesive. The composite fabric is obtained by calendering the fabric back and forth 5 times at 150°C.
[0094] According to GB / T 21196.2 2007 "Textiles - Martindale Method - Determination of Abrasion Resistance of Fabrics - Part 2: Determination of Specimen Breakage", the YG401H Martindale abrasion tester (Nantong Hongda Experimental Instrument Co., Ltd.) was used to rub the surface of the finished fabric until the surface pattern was damaged.
[0095] According to GB / T 8629-2017 "Textiles - Household washing and drying procedures for testing", the YG089S fully automatic fabric shrinkage tester (Nantong Hongda Experimental Instrument Co., Ltd.) was used to set the program to wash and dry the fabric.
[0096] According to ZF / T 60011-2016 "Test Method for Peel Strength of Composite Fabrics", the peel strength of the composite fabric before and after washing was tested using a YG026Q fabric strength tester (Ningbo Textile Instrument Factory).
[0097] The test results of the composite materials obtained using the adhesives of Examples 1-5 and Comparative Examples 1-2 are shown in Table 1:
[0098] Table 1
[0099]
[0100]
[0101] As shown in Table 1, the high-temperature resistant, two-component waterborne polyurethane adhesive prepared in this invention, when applied to the pattern on the fabric surface after hot stamping, still exhibits excellent high-temperature resistance and peel strength after washing.
[0102] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A high-temperature resistant, two-component waterborne polyurethane adhesive, characterized in that: Includes component A and component B; Component A, by mass percentage, comprises 10-20% organic polyisocyanate, 10-20% polyol, 0.1-1% catalyst, 2-6% chain extender, 3-8% end-capping monomer, 2-8% organic solvent, 1-3% salt-forming agent, and the balance being water. Component B, by mass percentage, comprises 10-15% organic polyisocyanate, 10-18% polyol, 2-8% organic solvent, and the balance being water.
2. The high-temperature resistant, two-component waterborne polyurethane adhesive according to claim 1, characterized in that: The mass ratio of component A to component B is 15 to 50:1; The viscosity of the high-temperature resistant, two-component waterborne polyurethane adhesive is 10,000–16,000 mPa·s.
3. The high-temperature resistant, two-component waterborne polyurethane adhesive according to claim 1, characterized in that: The high-temperature resistant, two-component waterborne polyurethane adhesive has a particle size ≤60nm; The absolute value of the Zeta potential of the high-temperature resistant, two-component waterborne polyurethane adhesive is >30mV.
4. The high-temperature resistant, two-component waterborne polyurethane adhesive according to claim 1, characterized in that: In component A, the organic polyisocyanate is selected from at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, 2,6-toluene diisocyanate and hexamethylene diisocyanate; The polyol is selected from at least one of polyethylene glycol 2000, polytetrahydrofuran glycol 2000, and polycarbonate glycol 2000.
5. The high-temperature resistant, two-component waterborne polyurethane adhesive according to claim 1, characterized in that: In component A, the catalyst is selected from at least one of dibutyltin dilaurate and stannous octoate; The chain extender is selected from at least one of dimethylolpropionic acid, dimethylolbutyric acid, sodium ethylenediamine ethanesulfonate, or 1,4-butanediol. The end-capping monomer is selected from at least one of aminopropyltrimethoxysiloxane, glycidoxypropyltrimethoxysilane, and aminopropyltriethoxysilane. The salt-forming agent is selected from any one of triethylamine, sodium hydroxide, or ammonia water; The organic solvent is selected from any one of butanone, tetrahydrofuran, and N-methylpyrrolidone.
6. The high-temperature resistant, two-component waterborne polyurethane adhesive according to claim 1, characterized in that: In component B, the organic polyisocyanate is selected from at least one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, 2,6-toluene diisocyanate or hexamethylene diisocyanate; The polyol is selected from at least one of polyethylene glycol 2000, polytetrahydrofuran glycol, ethylene glycol or trimethylolpropane; The organic solvent is selected from any one of butanone, tetrahydrofuran, or N-methylpyrrolidone.
7. A method for preparing a high-temperature resistant, two-component waterborne polyurethane adhesive according to any one of claims 1 to 6, characterized in that: Includes the following steps: (1) Under the action of a catalyst, organic polyisocyanate and dehydrated polyol are mixed to carry out the first reaction. When the -NCO content in the reaction system reaches the theoretical value, a chain extender is added to carry out the second reaction. Then, a capping monomer is added to carry out the capping reaction. Then, a salting agent and an organic solvent are added to carry out the neutralization reaction. Finally, water is added to carry out emulsification and dispersion, and vacuum distillation is performed to obtain component A. (2) The organic polyisocyanate, the dehydrated polyol and the organic solvent are mixed and carried out in the third reaction to obtain component B; (3) The components A and B are compounded to obtain the high-temperature resistant, two-component waterborne polyurethane adhesive.
8. The method for preparing a high-temperature resistant, two-component waterborne polyurethane adhesive according to claim 7, characterized in that: In step (1), the temperature of the first reaction is 60-100℃, and the reaction time is 2-3.5h; The temperature of the second reaction is 60–100°C, and the reaction time is 0.5–2 hours. The end-capping reaction is carried out at a temperature of 60–100°C for 0.5–1 hour. The neutralization reaction occurs at a temperature of 60–100°C for 0.5–1 hour. The emulsification and dispersion time is 0.5 to 1 hour.
9. The method for preparing a high-temperature resistant, two-component waterborne polyurethane adhesive according to claim 7, characterized in that: In step (2), the temperature of the third reaction is 70-90°C, and the time of the third reaction is 2-3.5 h.
10. The application of a high-temperature resistant, two-component waterborne polyurethane adhesive according to any one of claims 1 to 6, or a high-temperature resistant, two-component waterborne polyurethane adhesive obtained by the preparation method according to any one of claims 7 to 9, in hot stamping finishing of textiles.